2021
DOI: 10.1002/ece3.8155
|View full text |Cite
|
Sign up to set email alerts
|

Driven to the edge: Species distribution modeling of a Clawed Salamander (Hynobiidae: Onychodactylus koreanus) predicts range shifts and drastic decrease of suitable habitats in response to climate change

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Cautions are need for the growing amount of herpetofauna import 43 through the coasts. Since many studies revealed that herpetofauna of the Korean Peninsula are especially susceptible to climate change 28,[44][45][46] , the southern ecosystems need a particular conservation concern as habitats there will be disappeared sooner than later [45][46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…Cautions are need for the growing amount of herpetofauna import 43 through the coasts. Since many studies revealed that herpetofauna of the Korean Peninsula are especially susceptible to climate change 28,[44][45][46] , the southern ecosystems need a particular conservation concern as habitats there will be disappeared sooner than later [45][46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…A site where the species was found about 10 years ago by a ranger on the opposite side of the valley is now entirely dry and unlikely to support a breeding population, making habitat loss the main threat to the species. Climate change is also most likely to impact the species, as seen in other Hynobiids [64], and we can expect the distribution of the species to be contracting. It is, therefore, important to lower other stresses as amphibians can cope with a low number of conservation pressures, but populations crash when there are too many stress factors [65].…”
Section: Discussionmentioning
confidence: 99%
“…Regionally, mid‐southern areas of the Korean Peninsula will lose suitable habitat for O. spinalis by 2070. SDMs studies on species distributed in South Korea such as G. japonicus (Kim, Park, Bae, et al, 2020 ), Karsenia koreana (Borzée et al, 2019 ), and Onychodactylus koreanus (Shin et al, 2021 ) also showed that the suitable habitat will be shrunk gradually because of climate change. Considering that the O. spinalis populations are mainly distributed in southern Jeolla province, South Korea (Table 1 ), the threats to the species in South Korea might be severe by 2070 due to shrinking of suitable habitats in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Regionally, mid-southern areas of the Korean Peninsula will lose suitable habitat for O. spinalis by 2070. SDMs studies on species distributed in South Korea such as G. japonicus (Kim, Park, Bae, et al, 2020), Karsenia koreana (Borzée et al, 2019), and Onychodactylus koreanus (Shin et al, 2021) also showed that the suitable habitat will be shrunk gradually because of climate change.…”
Section: Discussionmentioning
confidence: 99%